Perbedaan Motivasi Belajar Anak Antara Menggunakan Model Belajar Sentra Dengan Model Belajar Kelompok Di Paud Kecamatan Tawangsari Sukoharjo Tahun 2013/2014 - Melliyana Putri, Ranny, Dr. Darsinah, M. Si (2015)
The purpose of this study was to determine the differences of motivation on learning by using a model of learning centers and early childhood learning model group in Tawangsari Sukoharjo Academic year 2013/2014. This study was conducted in kindergarten and early childhood Tawangsari with the sample of the kindergarten. The Ummi Kultsum to the application of the learning centers and Khazanah for the implementation of cooperative learning model. This study is a comparative descriptive study. The population of kindergarten and early childhood students in District Tawangsari Sukoharjo and samples used TK. Umm Kulthum as many as 20 students and a kindergarten. Khazanah as many as 20 students. Sampling using sampling random sampling technique. Methods of collection via questionnaires, data analysis using the ttest. The results of empirical research showed to 2,753 t, tt the degree of freedom that the significant level of 5% the amount of 2,020. to> tt on a significant level of 5% or 2.753> 2.020. Conclusion There are differences between children's learning motivation using a model of learning centers with the group in early childhood learning models Tawangsari Sukoharjo District of the academic year 2013/2014. The average child's motivation to learn by using better models of learning centers in the appeal with motivation to learn children using cooperative learning model.